(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2025)
This article aims to highlight some possible readings of Jean-François Lyotard’s Anima minima that, as things stand, appear to be under-researched, thus favouring the qualification of the French philosopher’s work as a mere ornament for his broader investigation on the sublime. As a framework, the article argues Lyotard’s parodic use of the concept of anima in relation to the original Aristotelian meaning, i.e. through a resemantisation such as to coincide with another Stagirite’s concept that is at its antipodes: that of automa. However the core of the work is the Lyotard’s interpretation through the semiotic of impulses developed by Pierre Klossowski in his Nietzsche and the Vicious Circle. Therefore emerges a characterisation of the concept of anima minima as the most radical of principles both for an aesthetics of contingency and for a perceptual model of the automa, in antithesis to an apophantic aesthetics of the subject.